Rivalrous Thinking and Athletes’ Behaviors Reflected in Janus Metz’s Borg vs McEnroe (2017) - Jesi Widayanti; Atinia Hidayah (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2020)
The purpose of this research is to analyze rivalrous thinking and its effect towards athletes’ behaviors in Janus Metz’s Borg vs McEnroe (2017). Researcher uses the qualitative descriptive design to examine the problem. The theory applied in this thesis is Adler’s individual psychology and rivalry approaches. The data collected from movie’s English subtitle by reading, identifying, classifying, and selecting relevant data. The results of the study are; first,the rivalrous thinking is raised by the rivals who involve in the rivalry and also the goal which becomes the object that those rivals are fighting over. Second, the rivalrous thinking affects the behaviors of Borg and McEnroe, then it comes to the conclusion in what type of personality they have.